2019
DOI: 10.1002/app.47446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified ZnO nanoparticle on the properties of polylactide ultrafine fibers

Abstract: Zinc oxide (ZnO) was modified with hexadecyltrimethoxysilane (HDTMS) to obtain hydrophobicity and used to reinforce polylactide (PLA), an environmentally friendly polymer. The PLA/HDTMS‐modified ZnO (m‐ZnO) nanocomposite prepared by adding m‐ZnO to the PLA matrix was fabricated into ultrafine fiber using electrospinning. Neat PLA and PLA/ZnO were used for comparisons. Structural analysis of the nanoparticles proved that the ZnO was modified successfully, and that the modification affected dispersibility and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…That is why various researchers have sought ways to reinforce this type of materials by incorporating nanoadditives that give rise to biocompatible and / or environmentally biodegradable polymeric nanocomposites. The most commonly used particles are pure hydroxyapatite, hydroxyapatite doped with some metal [16], calcium and phosphorus nanoparticles [17], tricalcium phosphate [18], copper sulphide [19], zinc oxide [20], oxide magnesium [21], strontium carbonate [22], montmorillonite [23], carbon nanotubes in conjunction with silver and iron nanoparticles [24], where each type of nanoparticle gives the polymer nanocomposite exclusive properties. Below are some examples of these types of compounds that have been used to generate technical textiles.…”
Section: Biodegradable Polymer Nanocomposites and Their Application Amentioning
confidence: 99%
“…That is why various researchers have sought ways to reinforce this type of materials by incorporating nanoadditives that give rise to biocompatible and / or environmentally biodegradable polymeric nanocomposites. The most commonly used particles are pure hydroxyapatite, hydroxyapatite doped with some metal [16], calcium and phosphorus nanoparticles [17], tricalcium phosphate [18], copper sulphide [19], zinc oxide [20], oxide magnesium [21], strontium carbonate [22], montmorillonite [23], carbon nanotubes in conjunction with silver and iron nanoparticles [24], where each type of nanoparticle gives the polymer nanocomposite exclusive properties. Below are some examples of these types of compounds that have been used to generate technical textiles.…”
Section: Biodegradable Polymer Nanocomposites and Their Application Amentioning
confidence: 99%
“…They created a nanocomposite comprising PLA and HDTMS-modified ZnO by adding the HDTMS-modified ZnO into the PLA matrix fabricated through the solvent casting process. According to the structural analysis of the nanoparticles, it was observed that ZnO was successfully modified and that the modification influenced both the dispersibility and hydrophobicity of the samples [ 33 ]. Shaker et al conducted an experiment to enhance the hydrophobicity of stainless steel by mixing it with sol–gel-based alumina and HDTMS.…”
Section: Introductionmentioning
confidence: 99%